2021
DOI: 10.1080/13621718.2021.1967013
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of ultrasonic spot welding of Cu/Ni dissimilar metals

Abstract: With increasing clamping pressure, the bond density increases, the effective thickness decreases, and the plastic deformation at the Cu side near the welding interface regions below the sonotrode tip peak and valley increases; the maximum lap shear tensile load is obtained at the clamping pressure of 0.5 MPa. In the case of the Cu/Ni joint prepared at the clamping pressure of 0.5 MPa, evident mutual diffusion and nanoscale wave-like pattern appear in the Cu/Ni interfacial area, bonding between Cu and Ni sheets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
(38 reference statements)
2
2
0
Order By: Relevance
“…Resulting in complex deformation at the faying interface between the two sheets and the formation of a wave-like shape instead of a flat outline. Similar results are reported by Ni et al [10], Li et al [8], Jedrasiak and Shercliff [36] and Chen et al [31]. It is beneficial to enhance the joint strength, as demonstrated by Prangnell et al [63].…”
Section: Simulation Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…Resulting in complex deformation at the faying interface between the two sheets and the formation of a wave-like shape instead of a flat outline. Similar results are reported by Ni et al [10], Li et al [8], Jedrasiak and Shercliff [36] and Chen et al [31]. It is beneficial to enhance the joint strength, as demonstrated by Prangnell et al [63].…”
Section: Simulation Resultssupporting
confidence: 85%
“…The highest plastic deformation is at the peak and valley of the indentation, here the stress is the maximum (Figure 13(a)). Similar results were reported by Ni et al [10], Li et al [19] and Du et al [25]. It can be observed that in the vibration direction, the compressive plastic strain is generated on the side of the peak, where the knurl is moving whereas the tensile is on the opposite side (Figure 13(b)).…”
Section: Plastic Strainsupporting
confidence: 88%
See 2 more Smart Citations